PEMAHAMAN TENTANG TEMATIK HADIS NABI MUHAMMAD SAW YANG BERKAITAN DENGAN HUKUM KELUARGA - Muhammad Yusuf Yahya; T Abrar ZA; Mohd. Salam; Sabda (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2026)
Hadith is the second primary source of Islamic law after the Qur'an and plays a significant role in explaining various aspects of life, including family law. This study aims to examine the development of Hadith from the era of Prophet Muhammad (peace be upon him) to the period of the Rightly Guided Caliphs (Khulafa al-Rashidin) and to analyze thematic Hadiths related to Islamic family law. This research employs a library research method using a descriptive-analytical approach based on Hadith literature, classical commentaries, and relevant academic sources. The findings reveal that the compilation and transmission of Hadith developed gradually, beginning during the Prophet’s lifetime and continuing through the efforts of the Companions, who exercised great caution in preserving the authenticity of Hadith. The thematic Hadith (maudhu’i) approach serves as an effective method for understanding Hadith by collecting and examining all narrations related to a specific topic. In the field of family law, the Prophet’s Hadiths provide comprehensive guidance regarding the rights and obligations of spouses, the protection of women, and the criteria for selecting a marriage partner. The Hadith prohibiting harsh treatment toward wives demonstrates Islam’s commitment to protecting women's dignity and rejecting domestic violence. Meanwhile, the Hadith encouraging Muslims to prioritize religious commitment when choosing a spouse emphasizes the importance of faith and piety as the primary foundation for establishing a harmonious, loving, and compassionate family (sakinah, mawaddah, wa rahmah). Therefore, thematic Hadiths on family law remain highly relevant in addressing contemporary family issues and serve as moral and normative foundations for strengthening Islamic family resilience.